Encapsulation of Gallic Acid with Acid-Modified Low Dextrose Equivalent Potato Starch Using Spray-and Freeze-Drying Techniques - Sepelevs Igor; Stepanova Valentina; Galoburda Ruta (Polish Journal of Food and Nutrition Sciences, 2018)
The main objective of the present study was to investigate the effect of spray- and freeze-drying techniques on the microencapsulation of a gallic acid compound using the acid-hydrolyzed low dextrose equivalent potato starch as a wall material. During the experiment, it was possible to achieve encapsulation efficiency of 70–84% for the freeze-dried and 65–79% for spray-dried samples, without statistically significant difference (P>0.05) in the encapsulation efficiency between the mentioned methods. Spray-dried samples formed spherical capsules with a higher number of micropores. Meanwhile, freeze-dried samples were shapeless, exposed larger pore volume (from 2.4×10−3 to 9.5×10−3 cm3/g against 1.2×10–3 4.9×10−3 cm3/g; analyzed by Barrett-Joyner-Halenda method) and overall higher surface area (0.632–1.225 m2/g against 0.472–1.296 m2/g; analyzed by Barrett-Joyner-Halenda method). Due to this fact, more gallic acid molecules were exposed to environmental factors and can be counted as losses. In addition, freeze-dried samples demonstrated lower water activity than spray-dried samples (0.075±0.014 against 0.178±0.008). Results showed that it is not practical to use freeze-drying for modelling encapsulation for food industry without a special necessity for protection of easily degradable chemical compounds. The present work makes a basis for the future studies of the microencapsulated phenolics application in food production.